Creating an outstanding college - O'Connell, Bernard J. (Cheltenham : Nelson Thornes, 2005)
'This book has been written following the experiences of one college and its transformation process. Using the example of Runshaw College's development, this book illustrates how to create a truly outstanding college. It offers active tools, approaches and methodologies that can support leaders as they endeavour to do the same.'--BOOK JACKET.
Includes bibliographical references (p. 227-232) and index.
Keywords: Runshaw College; Universities and colleges -- United Kingdom -- Administration; Junior colleges -- United Kingdom -- Administration -- Case studies